8 - Are the Covid-19 Pandemic and Public Procurement ‘Strange Bedfellows’? An African Perspective - Ismail Abdi Changalima, (Africa Development, 2023)
The purpose of this article is to provide insights into how the Covid-19 pandemic has affected public procurement operations, and the role of public procurement during the pandemic. The article synthesises relevant literature on Covid-19 and public procurement in the African context. A review of literature from 2020 to 2022 was done to enrich the findings of the current article, which shows that the Covid-19 pandemic affected public procurement in the form of delays, malpractice, budget reallocations and supply disruptions. Furthermore, during the Covid-19 pandemic it was recommended that public procurement practices be more strategic through collaboration, and respond more quickly in obtaining vaccines and health supplies, which were critical in the prevention and treatment of related illnesses. The article provides several practical implications in terms of ensuring good governance, implementing regulatory frameworks for emergency procurement, improving collaboration among members of comparable regional organisations, and implementing Covid-19 preventative measures. Finally, because the current study’s scope is limited in terms of the selection of published articles and other relevant literature that give insights about the African continent during this period, future studies could be conducted to include literature from outside the African continent in order to broaden the scope of this current study.